Reading in the Dark, Sleeping with the Lights On: Uses and Abuses of Horror in Children’s Literature - Kérchy, Anna (Hungarian Journal of English and American Studies, 2020)
Book review:McCort, Jessica R., ed. Reading in the Dark. Horror in Children’s Literature and Culture. Jackson: UP of Mississippi, 2016. pp. 256. ISBN 978-1496806444. Hb. $56.99.